Effects of Organizing Learning Activities Using Case-based Learning and Higher Order Questions on Media and Information Literacy of High School Students - Wadeesirisak, Prangtip; Makanong, Amporn (An Online Journal of Education, 2024)
This research aims to 1) compare students’ media and information literacy before and after employing a case-based learning approach combined with higher order questions, and 2) study students’ improvement in media and information literacy before, during, and after learning using this approach. The sample group used for the experiment consisted of grade 12 students at a school under the Nakhon Phanom Secondary Educational Service Area Office, selected using purposive selection, and the research method was a quasi- experimental design. The research instruments included an achievement test for evaluating students’ media and information literacy, observation forms, interview forms for evaluating students’ progress in media and information literacy, and lesson plans utilizing a case-based learning approach along with higher order questions. Quantitative data were analyzed by using mean, percentage, standard deviation, and t-test, while qualitative data were analyzed through content analysis. The findings showed that: 1) Mean post-test scores of students taught through learning activities using a case-based learning approach combined with higher order questions were significantly higher than pre-test scores at the 0.05 level of significance; and 2) students’ media and information literacy scores improved after the learning activities both in overall terms and when classified by each component.